2004
DOI: 10.1051/0004-6361:20047068
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newton survey of the Local Group galaxy M 33

Abstract: Abstract.In an XMM-Newton raster observation of the bright Local Group spiral galaxy M 33 we study the population of X-ray sources (X-ray binaries, supernova remnants) down to a 0.2-4.5 keV luminosity of 10 35 erg s −1 -more than a factor of 10 deeper than earlier ROSAT observations. EPIC hardness ratios and optical and radio information are used to distinguish between different source classes. The survey detects 408 sources in an area of 0.80 square degree. We correlate these newly detected sources with earli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 48 publications
6
117
0
Order By: Relevance
“…In this way, we selected 22 SNRs: the data sample is shown in Table 2. The first 3 columns report the SNR identification numbers in the various catalogs, respectively, Gordon et al (1998, labeled by "opt" in the table), Gordon et al (1999, labeled by "rad"), and Pietsch et al (2004; labeled by "xray"), while the next 3 columns show, respectively, the published linear (optical) diameters, 20 cm fluxes, and measured (i.e., absorbed) 0.2-4.5 keV fluxes.…”
Section: Results From An Independent Sample: M 33mentioning
confidence: 99%
“…In this way, we selected 22 SNRs: the data sample is shown in Table 2. The first 3 columns report the SNR identification numbers in the various catalogs, respectively, Gordon et al (1998, labeled by "opt" in the table), Gordon et al (1999, labeled by "rad"), and Pietsch et al (2004; labeled by "xray"), while the next 3 columns show, respectively, the published linear (optical) diameters, 20 cm fluxes, and measured (i.e., absorbed) 0.2-4.5 keV fluxes.…”
Section: Results From An Independent Sample: M 33mentioning
confidence: 99%
“…If we assume that we have identified all foreground star candidates from the optical correlation and inspection of the optical images, the remaining sources can be classified as SNR candidates using the criteria given in Table 6. Similar criteria were used to select supernova remnant candidates in XMM-Newton observations of M 33 (Pietsch et al 2004;Misanovic et al 2006). Ghavamian et al (2005) and Long et al (2010) confirmed the supernova remnant nature of many of these candidates based on optical and radio follow-up observations.…”
Section: Supernova Remnantsmentioning
confidence: 99%
“…The image bin size is 2 . The same procedure was applied in our previous M 31 and M 33 studies (PFH2005 and Pietsch et al 2004).…”
Section: Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…This pipeline was already used for the surveys of M31 (Pietsch et al 2005;Stiele et al 2011) and M33 (Pietsch et al 2004;Misanovic et al 2006). It was then enhanced for the analysis of the SMC survey by Richard Sturm (2012).…”
Section: Data Reductionmentioning
confidence: 99%